2020
DOI: 10.1186/s12935-020-01361-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four hub genes as promising biomarkers to evaluate the prognosis of ovarian cancer in silico

Abstract: Background: Ovarian cancer (OvCa) is one of the most fatal cancers among females in the world. With growing numbers of individuals diagnosed with OvCa ending in deaths, it is urgent to further explore the potential mechanisms of OvCa oncogenesis and development and related biomarkers. Methods: The gene expression profiles of GSE49997 were downloaded from the Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was applied to explore the most potent gene modules associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…In the past decades, vigorously developing high-throughput sequencing technology and computer-aided analytical methods have largely promoted the flourish of big data applications [ 20 22 ]. As an effective research strategy, transcriptome analysis has been widely used in several aspects of clinical or basic medical research [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, vigorously developing high-throughput sequencing technology and computer-aided analytical methods have largely promoted the flourish of big data applications [ 20 22 ]. As an effective research strategy, transcriptome analysis has been widely used in several aspects of clinical or basic medical research [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA analysis First, as precviously described, differentially expressed genes (DEGs) between EC and normal specimens in the TCGA dataset were screened out using the "limma" package with threshold of adjusted P-value < 0.05 and |log2FC| >1 [21]. Next the expression pro le of these DEGs was sent to establish a gene coexpression network by the weighted gene co-expression network analysis (WGCNA) package in R language as precviously described [22]. To matching the correlations with the nature regulation relationship, we built a scale-free topology to emphasize the strong correlations and attenuate the weak correlations with the soft threshold power of β = 3 (scale free R 2 = 0.85).…”
Section: Methylation and Mutantion Analysismentioning
confidence: 99%
“…In recent years, due to the continuous development and application of bioinformatics databases, more and more tumor biomarkers have been discovered [13][14][15][16]. At present, more and more studies have shown that EGFR family can be used as potential targets for the treatment of glioma [17,18].…”
Section: Introductionmentioning
confidence: 99%